(untitled) (Faridpur Medical College Journal, 2016)
Lymphangiomas are benign hamartomatous lymphatic tumours characterized by multiple communicating lymphatic channels and cystic spaces. Cystic lyphangiomas may be seen anywhere in the body but are common in neck, axilla, mediastinum and groin. Treatment options are surgical resection, radiation, sclerotherapy etc but have got high recurrence rate and complications. In the present study we hypothesized that complete surgical resection along with keeping a drain for 2-3 wks, may reduce recurrence rate. This prospective study was performed from July 2008 to June 2013. Total 21 children treated during this period by the technique of complete surgical excision with keeping drain tube in situ for 2 to 3 weeks. Ultrasound performed in all patients, CT scan and Duplex study performed in some patients, histopathology done in all patients. Patients with intra-abdominal lymphangioma not included in this study. Twenty one patients were operated during the study period and average duration of keeping drain tube was 18.57 days. Among the 21 cases 2 (9.52%) patients developed mild infection, 1 (4.76%) patient developed infection with pus formation and 1 (4.76%) patient developed recurrence. Our success in the treatment warrants further verification of potential benefits of keeping drain tube in situ for 2-3 weeks after surgical excision of lymphangiomas. Faridpur Med. Coll. J. Jan 2015;10(1): 26-28